Gibberellic acid promotes selenium accumulation in Cyphomandra betacea under selenium stress - Xu, Yaxin; Zhang, Lu; Wang, Jin; Liang, Dong; Xia, Hui; Lv, Xiulan; Deng, Qunxian; Wang, Xun; Luo, Xian; Liao, Ming’an; Lin, Lijin (Frontiers in Plant Science, 2022)
The selenium (Se) deficiency is threatening the human health, and the increase of Se content in food can prevent the Se deficiency of human body. To increase the Se content in fruit trees and alleviate the Se stress to fruit trees, the effects of gibberellic acid (GA) on the growth and Se accumulation in Cyphomandra betacea under Se stress were studied. Although GA increased the biomass of C. betacea, it did not significantly affect the root/shoot ratio. The root and shoot biomass had a quadratic polynomial regression relationship with the GA concentration. Furthermore, GA increased the photosynthetic pigment content, photosynthetic parameters, and antioxidant enzyme activity of C. betacea. GA also increased the Se content in C. betacea, peaking at 300 mg/L GA. For instance, GA (300 mg/L) increased the Se contents in roots and shoots of C. betacea by 70.31% and 22.02%, respectively, compared with the control. Moreover, the root Se and shoot Se contents had a quadratic polynomial regression relationship with the GA concentration. Correlation and grey relational analyses showed that the carotenoid, chlorophyll a, and chlorophyll b contents were closely related to the Se uptake in C. betacea under the GA application. These results show that GA (300 mg/L) can promote the growth and Se uptake of C. betacea under Se stress.